Comorbid psychopathology in binge eating disorder: relation to eating disorder severity at baseline and following treatment - Wilfley, D E; Friedman, M A; Dounchis, J Z; Stein, R I; Welch, R R; Ball, S A (Journal of consulting and clinical psychology, 2000)
Individuals with binge eating disorder (BED) have high rates of comorbid psychopathology, yet little is known about the relation of comorbidity to eating disorder features or response to treatment. These issues were examined among 162 BED patients participating in a psychotherapy trial. Axis I psychopathology was not significantly related to baseline eating disorder severity, as measured by the Structured Clinical Interview for DSM-III-R (SCID-I and SCID-II) and the Eating Disorder Examination. However, presence of Axis II psychopathology was significantly related to more severe binge eating and eating disorder psychopathology at baseline. Although overall presence of Axis II psychopathology did not predict treatment outcome, presence of Cluster B personality disorders predicted significantly higher levels of binge eating at 1 year following treatment. Results suggest the need to consider Cluster B disorders when designing treatments for BED.